The emergence of human prosociality: aligning with others through feelings, concerns, and norms - Jensen, Keith; Vaish, Amrisha; Schmidt, Marco F. H. (Frontiers in Psychology, 2014)
The fact that humans cooperate with nonkin is something we take for granted, but this is an anomaly in the animal kingdom. Our species’ ability to behave prosocially may be based on human-unique psychological mechanisms. We argue here that these mechanisms include the ability to care about the welfare of others (other-regarding concerns), to “feel into” others (empathy), and to understand, adhere to, and enforce social norms (normativity). We consider how these motivational, emotional, and normative substrates of prosociality develop in childhood and emerged in our evolutionary history. Moreover, we suggest that these three mechanisms all serve the critical function of aligning individuals with others: Empathy and other-regarding concerns align individuals with one another, and norms align individuals with their group. Such alignment allows us to engage in the kind of large-scale cooperation seen uniquely in humans.